The Impact of the 2011 Tunisian Revolution on Foreign Direct Investment - Algamoudi, Iheb; Štěrbová, Ludmila, 1957-; Jedlinský, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the impact of the 2011 Tunisian Revolution on foreign investment, focusing on agriculture and manufacturing. It analyzes how political instability and economic uncertainty affected investor confidence and sector performance. Using both primary data from questionnaires and secondary research, the study highlights shifts in investment trends, government reforms, and investor perceptions after the revolution. The findings show that while Tunisia has made efforts to improve its investment climate, ongoing challenges continue to affect its ability to attract and retain foreign investors.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses